The History of the Chemo-Free Model in the Treatment of Acute Promyelocytic Leukemia - Zhu, Hong-Hu (Frontiers in Oncology, 2020)
Acute promyelocytic leukemia (APL) has become a highly curable disease after four decades of endeavors. Thanks to the efforts of investigators throughout the world, the chemo-free concept has become a reality for both low- and high-risk patients. All-trans retinoic acid (ATRA) plus arsenic trioxide (ATO) without chemotherapy has become a first-line treatment for newly diagnosed APL and has been adopted in guidelines or expert recommendations from the NCCN and ELN and in China. Though the regimen has achieved great success, challenges still exist. The rate of early death still has not diminished significantly and is a major obstacle to curing all patients. Leukocytosis is the most important factor for ED, and completely abandoning chemotherapy is dangerous for certain patients in practice. To narrow the gap between guidelines and practice, this review aims to examine the history of the chemo-free model for the treatment of APL in the arsenic-alone era (1974–2002) and the arsenic plus ATRA era (2002–present) and provide practical considerations regarding early death.